Reducing patient delay in acute coronary syndrome: Randomized controlled trial testing effect of behaviour change intervention on intentions to seek help. Issue 1 (8th August 2022) - Farquharson, Barbara; Johnston, Marie; Williams, Brian; Smith, Karen; Dombrowski, Stephan; Jones, Claire; Treweek, Shaun; Dougall, Nadine; Grindle, Mark; Savinc, Jan; Abyhankar, Purva
Abstract: Objectives: The aim of this study was to evaluate the efficacy of a behaviour change intervention to reduce patient delay with symptoms of acute coronary syndrome. Design: A 3‐arm web‐based, parallel randomized controlled trial. Methods: The intervention comprised 12 behaviour change techniques (BCTs) embedded in a text‐only or text+visual narrative (the techniques were systematically identified through systematic review and a consensus exercise). Between February and November 2017, n  = 145 people who had recently experienced acute coronary syndrome were randomly allocated to intervention ('text+visual' or 'text‐only') or control. Intentions to phone an ambulance immediately for acute coronary syndrome symptoms were assessed before and after the intervention using symptom scenarios, and the change in intention was compared across the three groups. Results: Significant increases in intention to phone an ambulance immediately for ACS symptoms were seen following the 'text+visual' intervention but not following 'text‐only' or control. However, the study was underpowered to detect any significant changes in intention between the 3 groups. There were no unintended effects on intentions for non‐urgent symptoms. Conclusions: A 'text+visual' BCT‐based intervention may significantly increase intention to phone an ambulance with symptoms of ACS. Further testing of the effect of the intervention on actual behaviour is required.